Efficacy and safety of apatinib versus sorafenib/placebo in first-line treatment for intermediate and advanced primary liver cancer: A systematic review and meta-analysis - Peng, Dan; Cai, Yongqing; Chen, Geng; Hou, Min; Luo, Xiaofeng; Dongzhi, Zhuoma; Xie, Hongjun; Liu, Yao (Frontiers in Pharmacology, 2023)
Background: Apatinib was a novel tyrosine kinase inhibitor in treatment of advanced hepatocellular carcinoma (HCC). For decades, sorafenib had been a classic first-line treatment option for patients with HCC. This meta-analysis aimed to assess the efficacy and safety of apatinib versus sorafenib/placebo in first-line treatment of intermediate and advanced primary liver cancer (PLC). Methods: A literature search was performed via PubMed, Web of Science, CENTRAL, EMBASE, CNKI, VIP and CBM. Data of extraction is not restricted from databases of other languages. The Cochrane risk of bias tool, modified Jadad scale, Newcastle-Ottawa scale and ROBINS-I tool were employed to evaluate methodological qualities in original studies. Influence analysis was applied to assess the reliability of pooled results. Publication bias was evaluated with funnel plot, Begg’s test and Egger’s test. Results: 7 studies were included in the systematic review and meta-analysis. Both 4 randomized controlled trials and 1 clinical controlled trial were comparing apatinib with placebo, 2 retrospective clinical studies comparing apatinib with sorafenib. Apatinib led to the higher overall effects in objective response rate (ORR), disease control rate (DCR) and mean survival time (MST) over placebo (RR = 2.03, 95% CI: 1.46–2.81, P < 0.0001, I2 = 0%; RR = 1.17, 95% CI: 1.04–1.33, P = 0.009, I2 = 45.8%; SMD = 2.63; 95% CI, 1.47–3.78, P < 0.0001, I2 = 92.7%, respectively). Compared to sorafenib, apatinib showed no superiority in ORR and DCR, but was inferior in the 6-month and 1-year survival rate (RR = 1.99, 95% CI: 0.85–4.65, P = 0.111, I2 = 68.3%; RR = 1.04, 95% CI: 0.73–1.47, P = 0.840, I2 = 0.0%; RR =0.63, 95% CI: 0.42–0.97, P = 0.036, I2 = 0.0%; RR = 0.47, 95% CI: 0.29–0.79, P < 0.0001, I2 = 0.0%, respectively). Apatinib had the similar adverse effects over placebo, but possessed the greater incidence rate of proteinuria and hypertension over sorafenib. Conclusions: In first-line setting, apatinib might be an alternative treatment approach for intermediate and advanced patients with PLC. Sorafenib alone showed the better survival benefit within 1-year, and a lower incidence in hypertension and proteinuria than apatinib monotherapy.